Transcriptome Analysis of Bovine Rumen Tissue in Three Developmental Stages - Zhang, Yapeng; Cai, Wentao; Li, Qian; Wang, Yahui; Wang, Zezhao; Zhang, Qi; Xu, Lingyang; Xu, Lei; Hu, Xin; Zhu, Bo; Gao, Xue; Chen, Yan; et al. (Frontiers in Genetics, 2022)
Rumen development is a crucial physiological challenge for ruminants. However, the molecular mechanism regulating rumen development have not been clearly elucidated. In this study, we investigated genes involved in rumen development in 13 rumen tissues from three developmental stages (birth, youth and adult) using RNA-seq. We identified 6,048 genes were differentially expressed among three developmental stages. Using weighted correlation network analysis, we found 12 modules were significantly associated with developmental stages. Functional annotation and protein-protein interaction (PPI) network analysis revealed that CCNB1, CCNB2, IGF1, IGF2, HMGCL, BDH1, ACAT1, HMGCS2 and CREBBP involved in rumen development. Integrated transcriptome with GWAS information of carcass weight (CW), stomach weight (SW), marbling score (MS), backfat thickness (BFT), ribeye area (REA), and lean meat weight (LMW), we found up-regulated DEGs (foldchange 0~1) in birth-youth comparison were significantly enriched with GWAS signals of MS, down-regulated DEGs (foldchange >3) were significantly enriched with GWAS signals of SW, and foldchange 0~1 up/down-regulated DEGs in birth-adult comparison were significantly enriched with GWAS signals of CW, LMW, REA and BFT. Furthermore, we found GWAS signals for CW, LMW and REA were enriched in turquoise module, and GWAS signals for CW was enriched in lightgreen module. Our study provides novel insights into the molecular mechanism underlying rumen development in cattle, and highlights an integrative analysis for illustrating the genetic architecture of beef complex traits.